#133 Curcumin in-situ gel for the local treatment of periodontitis: Preparation, in-vitro evaluation and clinical assessment - Samal, Himansu Bhusan; Das, Itishree Jogamaya; Boyeena, Lavanya; Patra, Niranjan; S A , Sreenivas (Journal of Pharmaceutical Chemistry, 2022)
Periodontitis is one of the most widespread oral inflammatory infectious diseases affecting the oral cavity. This study aims to develop and characterize a more effective syringeable curcumin in-situ gel to treat Periodontitis and evaluate its clinical effectiveness. Curcumin in-situ gel was formulated by the cold method using temperature-sensitive (Poloxamer 188, 407), pH-sensitive (Carbopol 934P), and ion-sensitive (Gellan gum) polymer. Gel formulations including Poloxamer 407 and Carbopol 934P as independent factors for the selected response like viscosity and gelation temperature were optimized using central composite design (CCD). The formulation evaluations were made to ascertain drug content, gelation temperature, viscosity, stability, and in-vitro drug release. Appropriate physical characteristics for most formulations and their suitability for periodontitis were observed. Appropriate gelation temperature ranged from 30.2 to 36.5 °C, with a pH of 6.14 to 7.25. The viscosity of the gel at 40 °C ranged from 12540 to 32400 centipoise. In all cases, the designed formulations were successfully syringeable with a 21-gauge needle at cold temperature. Most of the formulations showed a greater correlation with the Higuchi equation, supporting the assumption that diffusion was the primary mechanism of drug release. Clinical study of the optimized gel formulation revealed a substantial reduction in the clinical markers of periodontitis. The study shows that Curcumin in-situ gel may be considered a promising delivery for the safe and efficient treatment of periodontitis which substantially overcomes the drawbacks of conventional therapy.